2023
DOI: 10.1186/s12870-023-04470-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomic and metabolomic analysis of alginate oligosaccharides alleviating salt stress in rice seedlings

You-Wei Du,
Ling Liu,
Nai-Jie Feng
et al.

Abstract: Background Salt stress is one of the key factors limiting rice production. Alginate oligosaccharides (AOS) enhance plant stress resistance. However, the molecular mechanism underlying salt tolerance in rice induced by AOS remains unclear. FL478, which is a salt-tolerant indica recombinant inbred line and IR29, a salt-sensitive rice cultivar, were used to comprehensively analyze the effects of AOS sprayed on leaves in terms of transcriptomic and metabolite profiles of rice seedlings under salt s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Salt stress is a common abiotic stress to crops and has become a serious environmental problem that affects plant growth and development. Recently, many studies have shown that plant seed germination is not significantly affected by low concentrations of salt stress, while higher concentrations of salt stress inhibit plant seed germination and the growth and development of seedlings [ 19 , 20 ]. Ren et al (2020) found that 100 mM NaCl stress significantly inhibited the development of pak choi ( Brassica chinensis L.) seed germination vigor, germination index, vigor index, and growth of the radicle and embryo [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress is a common abiotic stress to crops and has become a serious environmental problem that affects plant growth and development. Recently, many studies have shown that plant seed germination is not significantly affected by low concentrations of salt stress, while higher concentrations of salt stress inhibit plant seed germination and the growth and development of seedlings [ 19 , 20 ]. Ren et al (2020) found that 100 mM NaCl stress significantly inhibited the development of pak choi ( Brassica chinensis L.) seed germination vigor, germination index, vigor index, and growth of the radicle and embryo [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…7-a), suggesting a potential association between sucrose synthase and drought tolerance in sorghum. Alginate, a non-reducing disaccharide, plays a crucial role in mitigating drought [35] and salt stresses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Plants 2024, 13, x FOR PEER REVIEW 7 of 17 18.20%, respectively, in the leaves of both cultivars, while it significantly decreased stems' laccase activity by 10.68% of IR29.…”
Section: Effects Of Salt and Alginate Oligosaccharides On Lignin-rela...mentioning
confidence: 99%
“…AOS regulated the pectin, cellulose, and hemicellulose content of strawberry cell walls [17]. Our previous study demonstrated that alginate oligosaccharides specifically activated genes related to cell walls in rice under salt stress [18]. The regulatory mechanism of alginate oligosaccharides on rice cell wall metabolism under salt stress remains unclear.…”
Section: Introductionmentioning
confidence: 97%